Desarrollo de actividades didácticas multimedia complementarias para el software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos, geográficos y educativos del cantón Macará de la provincia de Loja - LLoglla Salas, Rosario Leonor (2015)
The current research detected the lack of didactic and multimedia activities as the main problem in teaching the Social Sciences. In addition, teachers are facing other problems such as: poor and limited training related to the use of new technological tools. This work was carried out in Macara in the province of Loja, at the elementary schools “10 de Agosto” located in the heart of the town, John F. Kennedy located in the parish General Eloy Alfaro in San Sebastian and Salvador Bustamente Celi in La Mandala town. To develop this research surveys were applied to teachers and students. These were undertaken in order to collect key information about the use of multimedia. Furthermore, a direct field observation was carried out in order to analyze the behavior of students in the class. Finally the didactic guides were analyzed and assessed enabling one to understand their usefulness. In conclusion it can be said that the development of multimedia activities will support and promote significant learning in learners as well as being useful and necessary for teachers enabling their use as didactic material in Social Studies classes when teaching historical, geographical and educational facts about the above mentioned town.